Keragaman Genetik DNA Mikrosatelit dan Hubungannya dengan Performa Bobot Badan pada Domba Lokal - C Sumantri; A Farajallah; J F Salamena (Media Peternakan, 2008)
The objectives of this study were to evaluate polymorphism of microsatellite DNA through the investigation of microsatellite loci of CSSM18, ILST54 and IDVGA30 and its possible association with body weight of local sheeps. A total of 266 head of DNA samples was collected from 8 local sheep populations, i.e. Garut fighting type from Ciomas-Bogor (25); Garut meat type from Margawati-Garut (29); thin tail sheep (TTS) from Jonggol-Bogor (33); and fat tail sheep (FTSs) from Indramayu (40), Madura (34), Sumbawa (26), Rote (35) and Donggala (44). Genetic polymorphism among groups of local sheep was calculated in frequency of alleles and genotypes. Association between genotypes and body weight was calculated by general linear model (GLM). Results showed that three loci showed high polymorphisms. CSSM18 locus had 12 genotypes with the highest frequency for CC (46,15%) then for AC (25,64%); whilst frequency of the other 10 genotypes providing AA, AE, BB, BC, BD, BE, CD, CE, DD and EE were less than 7%. IDVGA30 locus had 9 genotypes with three highest frequencies for DD (39,10%), CC (37,97%) and BB (10,90%); while the other 6 genotypes were less than 6 %. ILST54 locus had 8 genotypes with three highest frequencies for AA (39,85%), BB (21,43%) and BC (18,05%) respectively. It could be verified that local sheep possessing typical genotypes of CE in CSSM18 locus and CD in IDVGA30 locus was apparently related with a higher body weight compared to another genotypes; on the contrary, those possessing DD genotypes in ILSTS54 was seemingly associated with a lower body weight. Key words: local sheep, microsatellite DNA, genotypes, body weight